The role of identity in the development of depressive, anxiety and psychosis symptoms in adolescents exposed to childhood adversity: a process-oriented approach - Samaey, Celine; Lambrechts, Stijn; Lecei, Aleksandra; Achterhof, Robin; Hagemann, Noëmi; Hermans, Karlijn S. F. M.; Hiekkaranta, Anu P.; Kirtley, Olivia J.; Reininghaus, Ulrich; Boets, Bart; Myin-Germeys, Inez; van Winkel, Ruud (BMC psychiatry, 2025)
Childhood adversity is known to predispose to a wide array of psychopathology in adolescence and early adulthood. Identity development, being a crucial developmental task during adolescence, has been suggested to affect this association. Nonetheless, research on the role of identity processes is scarce. The current study aims to investigate how identity processes of exploration and commitment may impact the association between childhood adversity and psychopathology.